Pericyte Progenitor Coupling to the Emerging Endothelium During Vasculogenesis via Connexin 43 - Payne, Laura Beth; Tewari, Bhanu P.; Dunkenberger, Logan; Bond, Samantha; Savelli, Alyssa; Darden, Jordan; Zhao, Huaning; Willi, Caroline; Kanodia, Ronak; Gude, Rosalie; Powell, Michael D.; Oestreich, Kenneth J.; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2022)
Vascular pericytes stabilize blood vessels and contribute to their maturation, while playing other key roles in microvascular function. Nevertheless, relatively little is known about involvement of their precursors in the earliest stages of vascular development, specifically during vasculogenesis. We combined high-power, time-lapse imaging with transcriptional profiling of emerging pericytes and endothelial cells in reporter mouse and cell lines. We also analyzed conditional transgenic animals deficient in (connexin 43/gap junction alpha-1) expression within Ng2+ cells. A subset of cells, likely pericyte/mural cell precursors, arose alongside endothelial cell differentiation and organization and physically engaged vasculogenic endothelium in vivo and in vitro. We found no overlap between this population of differentiating pericyte/mural progenitors and other lineages including hemangiogenic and neuronal/glial cell types. We also observed cell-cell coupling and identified Cx43-based gap junctions contributing to pericyte-endothelial cell precursor communication during vascular assembly. Genetic loss of in pericyte progenitors compromised embryonic blood vessel formation in a subset of animals, while surviving mutants displayed little-to-no vessel abnormalities, suggesting a resilience to loss in Ng2+ cells or potential compensation by additional connexin isoforms. Together, our data suggest that a distinct pericyte lineage emerges alongside vasculogenesis and directly communicates with the nascent endothelium via Cx43 during early vessel formation. loss in pericyte/mural cell progenitors can induce embryonic vessel dysmorphogenesis, but alternate connexin isoforms may be able to compensate. These data provide insight that may reshape the current framework of vascular development and may also inform tissue revascularization/vascularization strategies.